Strategi Peningkatan Self Efficacy pada Guru dalam Penanganan Siswa Berkebutuhan Khusus - Rahmawati Prihastuty; Sugiariyanti; Fatma Kusuma Mahanani; Dyah Ayu Rahmawati; Firdaus, Aina Aulia; Filea Suryaningtyas (Jendela Akademika: Jurnal Pengabdian Kepada Masyarakat, 2024)
Children with special needs are children who experience growth and development disorders characterized by limitations in one or more physical and psychological abilities that can hinder the learning process so that they need services that suit their needs. As educators, teachers in inclusive schools face the challenge of providing special treatment and approaches to their students so that students with special needs can follow the learning process optimally. Therefore, it is necessary for a teacher to have high self-efficacy so that the objectives of implementing learning activities can be achieved optimally. The service team offers a solution in the form of education and strengthening self-efficacy for teachers of TK Pembina ABA 54 Semarang which aims to increase self-efficacy, so that teachers can handle students with special needs and the learning process runs effectively. Activities are carried out using psychoeducational methods and to determine the improvement that occurs. Participants were given a pretest and posttest, and it was found that there was an increase in self-efficacy and stress management in teachers. Psychoeducation conducted to provide knowledge about self-efficacy and stress management efforts showed that there was a significant decrease in stress with a significantly increased level of self-efficacy.